Louisiana : The Collection and Buildings. - Jensen, Knud W. (Humlebaek : Louisiana Museum of Modern Art, 1988)
Agam, Yaacov ; Albers, Josef ; Alechinsky, Pierre ; Appel, Karel ; Dietman, Erik ; Dibbets, Jan ; Erro ; Fontana, Lucio ; Gorin, Jean ; Immendorff, Jörg ; Kelly, Ellsworth ; Martin, Etienne ; Morellet, François ; Reed, David ; Scully, Sean ; Rothko, Mark ; Twombly, Cy ; Walker, John ; etc.
boek